Motivasi Pembajakan Software: Perspektif Mahasiswa - Fathul Wahid (Seminar Nasional Aplikasi Teknologi Informasi (SNATI), 2004)
The study aims to investigate (1) pattern of software piracy among Indonesianstudents?; and (2) motivating factors of the piracy? A survey to 122 undergraduate studentsin informatics discloses that rate of the software piracy among students is high. This finding isin line with the global software piracy statistics show that the piracy rate in Indonesia is veryhigh, though revenue loss to the piracy is very small (1.1%) when compared to that in US andCanada. Unaffordable price of legal software is the dominant reason. Software pricediscrimination, enacting and reinforcing appropriate law consistently, and encouraging touse open source software are recommended to combat the piracy.Keywords: software piracy, motivation, price discrimination.